O espaço comunicativo do aposentado da UFU (2009-2014) - Santos, Rosane Cristina de Oliveira (2014)
The population ageing arises like a change in the socioeconomic context and constitutes a relevant theme in the construction of the oldness image, as the questions about retirement. The servers, who are inside this context, may face the fear and the lack of information about their rights. And with the aim to help the workers in the transition work-retirement, to make it happen in an easy way, arises this question: Which is the best behavior to minimize the anguish purchased of retirement without a preparation for the new stage of life? In this way, the general objective is examining the communicative space of the retired importance of UFU, between 2009 and 2014, from two perspectives: the presence speeches, and the news in the social networks. This research was developed in the Pos-graduation Program in Technology, Communication and Education of Education College of Federal University of Uberlandia - main line of research in Technology and Communication Interfaces, in the subject of the cultural problems of the communicative process: media, culture and memory. This is an exploring research, with bibliographic nature, using the analysis and cultural method. This analysis is structured in the borderline of concepts like, work, oldness, quality of life and technology, based in the discussion about cultural studies. The research produces one analysis of an attendance course to prepare to retirement; argues about the question of the retired people, based in the analysis of UFU portals, and examine, from other sites, the programs and speeches, the methodologies and information concepts for the retirement preparation. The conclusion of the research identifies that: as the face to face course, as the information in the site of UFU, are not sufficient for the appreciation of the servers in the retirement process. Added to this, the university must build references that makes the retired person recognize himself as a man in the space who acted during a long period of his lifetime.